2009
DOI: 10.1016/j.agee.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Soil characteristics under cash crop farming in upland areas of Sarawak, Malaysia

Abstract: This study discusses soil fertility under perennial cash crop farming (para rubber, Hevea brasiliensis; black pepper, Piper nigrum; oil palm, Elaeis guineensis) conducted by local farmers and an oil palm estate in an upland area of Sarawak, Malaysia, in comparison with the surrounding secondary forests. In the farmlands of the local farmers, rubber farming was conducted without fertilizer application, while 2 to 5 t ha-1 of NPK compounds were applied annually on pepper farms. Soils under rubber farming were ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 24 publications
6
40
3
Order By: Relevance
“…High correlations of clay contents were found with pH, CEC, ECEC, and exchangeable Al ( Table 5), indicating that clay content is a determinant factor for soil acidity and cation retention capacity of soils. In contrast, T-C contents at the 0-10 cm layer were not correlated with clay contents, CEC or ECEC across all of the study sites nor within each land uses although the previous studies reported significant correlation between clay and T-C contents and between the T-C contents and CEC or ECEC in the surface soils (Ohta and Effendi 1992b, Ohta et al 1993, Tanaka et al 2007, 2009). Relatively clay-rich soils including the four PLF soils were distributed in the belt perpendicular to Kahayan River.…”
Section: Clay Contents and The Role Of Clay As The Determinant Factormentioning
confidence: 56%
See 3 more Smart Citations
“…High correlations of clay contents were found with pH, CEC, ECEC, and exchangeable Al ( Table 5), indicating that clay content is a determinant factor for soil acidity and cation retention capacity of soils. In contrast, T-C contents at the 0-10 cm layer were not correlated with clay contents, CEC or ECEC across all of the study sites nor within each land uses although the previous studies reported significant correlation between clay and T-C contents and between the T-C contents and CEC or ECEC in the surface soils (Ohta and Effendi 1992b, Ohta et al 1993, Tanaka et al 2007, 2009). Relatively clay-rich soils including the four PLF soils were distributed in the belt perpendicular to Kahayan River.…”
Section: Clay Contents and The Role Of Clay As The Determinant Factormentioning
confidence: 56%
“…The levels of T-C and T-N both at the 0-10 cm and 30-40 cm layers were also similar to or higher than those not only reported in these studies but also those under secondary forest and farmlands (Kleinman et al 1996, Lawrence et al 2001, Tanaka et al 2007, 2009). The C/N ratios were 13.1 on average across the study sites and lower than the values of more than 15 reported in the most of these previous studies.…”
Section: Soil Organic Matter and Bulk Densitymentioning
confidence: 56%
See 2 more Smart Citations
“…Further, studies have demonstrated that the loss of organic matter through the conversion of forest to plantation results in higher Bd values [38]. In addition, the high Bd values are an indicator of soil compaction in plantations [39].…”
Section: Effect Of Soil Depth and Land Cover On Physiochemical Propermentioning
confidence: 99%